Diversity and Distribution of Myrmecophytes in Bengkulu Province - Safniyeti Safniyeti; Sulistijorini Sulistijorini; Tatik Chikmawati (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2017)
Myrmecophyte is a common medicinal plant used by local people in Indonesia for treating various diseases especially in Papua. Bengkulu province is one of the Myrmecophyte habitats, but there has no report on its identity and distribution. The objectives of this research were to identify the diversity and analyze the Myrmecophytes distribution as well as factor affecting its presence. This study used purposive sampling method by exploring the area where Myrmecophytes commonly found. The Myrmecophyte distribution based on host tree was analyzed using Morishita index and the autecological analysis of abiotic factors was performed using Principal Component Analysis (PCA) generated from Minitab 16. The results of this research showed that there were two species of Myrmecophytes in Bengkulu province, namely Hydnophytum formicarum and Myrmecodia tuberosa, as well as two variants of M. tuberosa i.e. M. tuberosa ‘armata’ and M. tuberosa ‘siberutensis’. The distribution of Myrmecophytes based on host tree was mostly randomly scattered in Central Bengkulu regency, Seluma, North Bengkulu, South Bengkulu, and Kaur. Their distributions were affected by light intensity and temperature. The data of this research can be used as basic information for carried out conservation efforts in Bengkulu province. The abundance of Myrmecophytes is also used as a source of additional income for local people in Bengkulu province.